Western diet induces endogen oxidative deoxyribonucleic acid damage and infl ammation in Wistar rats - YENER, Yeşim; Hümeyra YERLİKAYA, Fatma (Revista de Nutrição, 2023)
Objective Nutritional diseases such as metabolic syndrome, cardiovascular disorder, chronic infl ammation or even cancer are observed in people who sustain their lifestyle by Western diet due to high calorie intake. The origin of these diseases are the degraded deoxyribonucleic acid structure. In this study, we investigated whether Western diet produced endogenous oxidative deoxyribonucleic acid damage, apoptosis or infl ammation. Methods Twenty-eight male Wistar rats, aged 10-12 weeks, were divided into four groups. The rats in control group received the standard diet and the remaining rats were given one of the following three diets for four weeks: a high-fat diet containing 35% fat, a high-sucrose diet containing 69% sucrose and Western diet comprising both two types of diets. After treatment the serum 8-hydroxy-2-deoxyguanosine, poly (adenosine diphosphate ribose) polymerase-1, chitinase-3-like protein 1, soluble urokinase-type plasminogen activator receptor, Fas ligand and cytochrome c levels were measured. Results It was observed no changes in the serum soluble urokinase-type plasminogen activator receptor, Fas ligand and cytochrome c levels whereas a statistically signifi cant increase in the serum 8-hydroxy-2-deoxyguanosine, poly (adenosine diphosphate ribose) polymerase-1 and chitinase-3-like protein 1 levels were found only in rats that were given Western diet. Conclusion The findings show that Western diet produced endogenous oxidative deoxyribonucleic acid damage, which then increased serum poly (adenosine diphosphate ribose) polymerase-1 levels, eventually leading to inflammation.